Self Esteem Dan Kepatuhan Pembatasan Cairan Pada Pasien Yang Menjalani Hemodialisis Di RSUD Dr. Harjono Ponorogo - Isro'in, Laily; Munawaroh, Siti; Restiani, Dila (Jurnal Keperawatan Muhammadiyah, 2024)
To determine the relationship between self-esteem and adherence to fluid restriction in patients undergoing hemodialysis at Dr. Hospital. Harjono PonorogoThis research article is a quantitative study using a correlational design with a cross-sectional approach. The population in this study were all patients undergoing hemodialysis at RSUD Dr. Harjono Ponorogo as many as 165 respondents. The sampling technique using purposive sampling obtained a sample of 104 respondents. Data collection using the Coopersmith Self Esteem Inventory (CSEI) questionnaire and the fluid restriction compliance questionnaire from Senny Nur Wulan (2016). The data was then subjected to univariate and bivariate analysis, as well as statistical tests such as the Chi-Square test.Â The results of this study indicate that out of 104 respondents at RSUD Dr. Harjono obtained the results that most of the 63 respondents (60.6%) had a high level of self-esteem and most of the 54 respondents (51.9%) did not comply with fluid restrictions. The results of statistical tests using the Chi-Square test obtained p value = 0.003 < (0.05) meaning that there is a relationship between self-esteem and compliance with fluid restrictions in patients undergoing hemodialysis at Dr. Hospital. Harjono Ponorogo.There is a relationship between self-esteem and compliance with fluid restrictions in patients undergoing hemodialysis at RSUD Dr. Harjono PonorogoÂ